The transformation process of Polish economy, an economic miracle? - Escribano López, Alberto (Papeles de Europa, 2020)
Since 1989, Poland's economy has undergone a successful process of economic transformation. In the economic literature, the success of this process is associated with the neoliberal policies applied during the first years of the 90s, shock therapy. However, throughout this investigation the success of the process of transformation of Poland's economy will be considered not the result of the effective application of political policies, but that the subsequent success reaped could not be understood without the policies oriented towards accumulation and without Poland's accession to the EU, which has allowed us to reach important levels of socio-economic development.Macroeconomically, the transformation process is seen as a successful process, which has helped Poland prosper economically and socially; but from the social perspective and the weight of the progress made, the transformation process has not led to a specific improvement in the problems of life that needed to equip Poland with the most advanced countries in the European Union.
Keywords: economic transformation; economic success; shock therapy; European Union; social improvement